Design and experimental validation of a physics-based oxygen storage — thermal model for three way catalyst including aging. (November 2017) - Sabatini, Stefano; Gelmini, Simone; Hoffman, Mark A.; Onori, Simona
Abstract: In this paper, a physics-based, oxygen storage-thermal model for a three way catalyst (TWC) is developed and experimentally validated. This model is then extended to account for aging impacts on the TWC. In order to identify the model parameters, a series of ad hoc experiments were designed to test the device over various engine operating conditions. Four TWCs of different ages were tested to investigate the effects of TWC aging on the oxygen storage dynamics. Results show that aging can be lumped within a single model parameter, referred to as oxygen storage capacity . Sensitivity analysis shows only negligible dependence of oxygen storage capacity on catalyst operating temperature. The comprehensive model is validated over real driving conditions for different catalyst ages. The developed model has the potential to enhance the design of optimization-control techniques for fuel consumption benefits and on-board diagnostics health measurement robustness.